1974
DOI: 10.1073/pnas.71.10.3824
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin Endoperoxides. A New Concept Concerning the Mode of Action and Release of Prostaglandins

Abstract: Methods were developed for quantitative determination of the three major metabolites of arachidonic acid in human platelets, i.e., 12L-hydroxy-5,8,10,-14-eicosatetraenoic acid (HETE), 12L-hydroxy-5,8,10-heptadecatrienoic acid (HHT) and 8-(1-hydroxy-3-oxopropyl)-9,12L-dihydroxy-5,10-heptadecadienoic acid (PHD). Aggregation of washed platelets by thrombin was accompanied by release of 1163-2175 ng/ml of HETE, 1129-2430 ng/ml of HHT, and 998-2299 ng/ml of PHD. The amount of PGG2 (prostaglandin G2) produced as cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
112
0
4

Year Published

1978
1978
2008
2008

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 415 publications
(120 citation statements)
references
References 19 publications
4
112
0
4
Order By: Relevance
“…The results of this study showed that the synthesis of thromboxane was not inhibited by FAD at any time of incubation periods, while it was markedly inhibited by aspirin, which is a well known inhibitor of cyclooxygenase (Hamberg, Svensson and Samuelsson 1974). A part of the results obtained in the present experiments is shown in Fig.…”
Section: Effects Of Fad On the Platelet Aggregation And Atp Release Isupporting
confidence: 62%
“…The results of this study showed that the synthesis of thromboxane was not inhibited by FAD at any time of incubation periods, while it was markedly inhibited by aspirin, which is a well known inhibitor of cyclooxygenase (Hamberg, Svensson and Samuelsson 1974). A part of the results obtained in the present experiments is shown in Fig.…”
Section: Effects Of Fad On the Platelet Aggregation And Atp Release Isupporting
confidence: 62%
“…Thromboxane B2 is apparently formed from its unstable precursor thromboxane A2 [3]. The generation of thromboxane AZ required the presence of an active platelet microsomal fraction.…”
mentioning
confidence: 99%
“…Its formation was suggested to play a key role in arachidonic-acid-induced platelet aggregation [3]. In contrast, no distinct physiological role has yet been observed or suggested for 120H-17:3.…”
mentioning
confidence: 99%
See 2 more Smart Citations